Determination of Extreme Points in the Profile Grinding Process Based on Form Grinding in the Wind Power Generating Field - Wang Jiong; Yu Shihang; Sun Yuwen (Jixie chuandong)
As one of the most important types of energy, wind power generated electricity is used more and more commonly. For the system of wind power generated electricity, gear box is a key assembly and directly determines its performance. The surface accuracy of gears is one of the key factors which influence the gear box's property. Nowadays, blanks of wind power generating gears are often derived by hobbing and the finishing process is completed using the profile grinding method. In this process, extreme grinding points are very important for studying grinding process, optimizing grinding parameters and eliminating machining deficiencies. Therefore, a new method to determine extreme grinding points is proposed. Based on the meshing principle, surfaces of gear teeth are obtained. Using the profile grinding method, the model for determining extreme grinding points is developed and an iterative way is used to get the points. One example using typical wind power generating gears is carried out to illustrate the correctness and validity of the proposed method.